2018
DOI: 10.1002/pon.4941
|View full text |Cite
|
Sign up to set email alerts
|

Relationship status and quality of the partner relationship in parents of long‐term childhood cancer survivors: The Swiss Childhood Cancer Survivor Study‐Parents

Abstract: Objective: The intensive and long-lasting experience of childhood cancer is a tremendous stressor for the parental relationship. We aimed to (1) compare civil status and partner relationship of parents of long-term childhood cancer survivors with population-based comparisons, (2) identify cancer-related characteristics associated with not being married, and (3) evaluate the quality of the partner relationship. Methods:We sent questionnaires to parents of survivors aged ≤16 years at diagnosis and ≥20 years at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Most parents adapted well to cancer-related changes in their partner relationship and reported a strengthened bond. A recent large-scale study which investigated the relationship status and quality of parents of long-term childhood cancer survivors found an increased dependency within the partner relationship in terms of solving problems together and having a particularly close relationship 32. Our qualitative results show that these effects already occur in an early stage of survivorship.…”
Section: Discussionsupporting
confidence: 49%
“…Most parents adapted well to cancer-related changes in their partner relationship and reported a strengthened bond. A recent large-scale study which investigated the relationship status and quality of parents of long-term childhood cancer survivors found an increased dependency within the partner relationship in terms of solving problems together and having a particularly close relationship 32. Our qualitative results show that these effects already occur in an early stage of survivorship.…”
Section: Discussionsupporting
confidence: 49%
“…Yet a previous study also found differences in agreement on and off treatment, although this study investigated child proxy agreement instead of parental agreement [19]. Especially during the child's cancer treatment the primary caregiver is likely to be more closely involved with the child than the second caregiver [32,33]. It might be that this could either enhance or relieve the worries of the second parent, considering the bidirectional differences that we found in the proxy ratings, but this warrants further research.…”
Section: Main Findings and Implicationsmentioning
confidence: 77%
“…41 Additionally, a recent study in parents of long-term childhood cancer survivors showed greater dependency in the parental relationship as compared to population-based controls, with mothers being the primary caregivers and fathers the breadwinners. 42 In our study sample, mean hour of employment was 24 h for employed mothers versus 38 h for fathers. Moreover, more mothers in our study reported parenting problems when compared to fathers (37% vs 24%, respectively), which might also indicate that mothers were more closely involved in the caregiving process.…”
Section: Additionally Mothers With a Non-dutch Background Reported Lmentioning
confidence: 80%
“…Furthermore, results of a Dutch study in parents of children with a chronic illness showed that caring for an ill child leads to an even wider gap between maternal and paternal labor force participation . Additionally, a recent study in parents of long‐term childhood cancer survivors showed greater dependency in the parental relationship as compared to population‐based controls, with mothers being the primary caregivers and fathers the breadwinners …”
Section: Discussionmentioning
confidence: 99%